2023
DOI: 10.3390/jpm13030461
|View full text |Cite
|
Sign up to set email alerts
|

Considerations for Satisfactory Sedation during Dental Implant Surgery

Abstract: Implant surgery is a lengthy dental procedure, and sedation is often used to reduce discomfort. The effectiveness of sedation has traditionally been evaluated in terms of patient and surgeon satisfaction, but the most important goal is not to induce a deep sleep in the patient, but rather to ensure that the surgery is performed safely and as planned. Additionally, adequate pain control is a necessary requirement for patient and surgeon satisfaction. Most patients undergoing implant surgery are middle-aged or o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 105 publications
(121 reference statements)
0
3
0
Order By: Relevance
“…Full texts of the remaining 15 studies were reviewed in detail. Of these, eight studies were further excluded because seven studies did not include older patients [ 23 , 24 , 25 , 26 , 27 , 28 , 29 ] and one study was a review [ 30 ]. The kappa value for the articles selected by the two investigators was 0.875.…”
Section: Resultsmentioning
confidence: 99%
“…Full texts of the remaining 15 studies were reviewed in detail. Of these, eight studies were further excluded because seven studies did not include older patients [ 23 , 24 , 25 , 26 , 27 , 28 , 29 ] and one study was a review [ 30 ]. The kappa value for the articles selected by the two investigators was 0.875.…”
Section: Resultsmentioning
confidence: 99%
“…However, few reports exist on procedural sedation using continuous intravenous administration of remimazolam. As a mild-to-moderate level of sedation allowing for some degree of consciousness is deemed appropriate for dental procedures [ 41 , 42 ], in this study, we determined the dose of remimazolam administration based on the findings of Schüttler et al, who reported that a remimazolam Ce of 0.34 µg/mL corresponded to a MOAA/S score of 4 (indicating a lethargic response of the patient to their name spoken in a normal tone) [ 27 ]. We adopted Masui’s pharmacokinetics model [ 13 , 14 ] and set the initial remimazolam loading dose to 0.05 mg/kg, followed by an initial continuous infusion rate of 0.35 mg/kg/h, aiming to maintain a simulated remimazolam Ce of approximately 0.34 µg/mL during the maintenance phase of anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…The MOAA/S score was used to clinically assess the depth of sedation. In dental procedures, moderate sedation is often the desired level, where patients can respond purposefully to verbal commands, corresponding to a MOAA/S score of 3 [ 22 , 41 , 42 ]. Therefore, in this study, remimazolam dosing was adjusted to achieve a MOAA/S score of 2–4.…”
Section: Discussionmentioning
confidence: 99%